Management of Farmer Groups in Increasing Salt Production in Siduwonge Village, Randangan District, Pohuwato Regency of Gorontalo Province - Venny Lanti; Yosep P. Koton; Lisda Van Gobel (LP2M Universitas Bina Mandiri Gorontalo, 2022)
The research objective was to determine and analyze: (1) Management of the Community Salt Business Group (KuGAR) (2) Inhibiting factors for the management of the Community Salt Business Group (KuGAR) in increasing the production of people's salt in Siduwonge Village, Randangan District, Pohuwato Regency, Gorontalo Province. This study used a descriptive qualitative approach, with a focus on Farmer Group Management and Inhibiting Factors in increasing People's Salt Production. The methods used in this research are observation, interview, and documentation. Data were analyzed using Miles and Huberman methods, namely data reduction, data presentation, and verification. The results showed that: (1) Management of the People's Salt Business Group (KuGAR) from the planning aspect, there is no SOP document for salt production techniques and salt business financing plans. From the aspect of assistance, it is still administrative assistance and the limitations of education and training activities for business actors and from the results of an evaluation of production reports have not been carried out independently by groups; (2) Inhibiting factors that affect the increase in people's salt production are inadequate infrastructure and facilities, availability of routine weather information and access to marketing salt.